Effect of the training process of high-class and elite sprint swimmers of both genders on the state of the autonomic nervous system, central hemodynamics and physical working capacity - Mykhaliuk, Ye. L.; Horokhovskyi, Ye.; Михалюк, Євген Леонідович; Гороховський, Є. (My University, 2022)
Purpose: to investigate the influence of the training process of high-class and elite sprint swimmers of both genders on the parameters of the autonomic nervous system, central hemodynamics and physical working capacity. Material & Methods: in the preparatory period of the training process, 145 sprint swimmers (56 females and 89 males) with sports qualifications from CMS (high-class swimmers) to MS-MSIC (elite swimmers) were examined, of which 56 sprint swimmers (31 females and 25 males) in 2006 and 89 sprint swimmers in 2021 (25 females and 64 males). To assess the autonomic regulation of cardiac activity time- and frequency domain methods of HRV analysis were used. Central hemodynamic parameters were examined by an automated tetrapolar rheography. Physical working capacity was measured according to a common technique on a cycling ergometer using a submaximal PWC170 test and calculating the relative value of physical working capacity, i.e. PWC170/kg. Мета: дослідити вплив трен-увального процесу висококласних та елітних плавців-спринтерів обох статей на показники автономної нервової системи, центральної гемодинаміки та фізичну працездатність. Матеріал і методи: обстежено 145 плавців-спринтерів (56 жінок та 89 чоловіків) рівня від КМС до МС-МСМК у підготовчому періоді тренувального процесу, з них у 2006 році 56 плавців-спринтерів (31 жінка та 25 чоловіків) та у 2021 році 89 плавців-спринтерів (25 жінок та 64 чоловіки). Для аналізу вегетативної регуляції серцевої діяльності використовували часові та спектральні показники ВСР. Центральну гемодинаміку вивчали методом автоматичної тетраполярної реографії. Визначення фі-зичної працездатності здійснювали за за-гальноприйнятою методикою на велоергометрі з використанням субмаксимального тесту PWC170.
Вплив тренувального процесу висококласних та елітних плавців-спринтерів обох статей на стан автономної нервової системи, центральну гемодинаміку та фізичну працездатність
Mykhaliuk Ye. L. - https://orcid.org/0000-0003-3607-7619
Keywords: high-class and elite swimmers of both genders; heart rate variability; central hemodynamics; physical working capacity; плавці високого класу та елітні плавці обох статей; варіабельність серцевого ритму; центральна гемодинаміка; фізична працездатність